1978
DOI: 10.1103/physrevlett.41.1257
|View full text |Cite
|
Sign up to set email alerts
|

Spin Dependence of High-P2ElasticppScattering

Abstract: We measured da/dt forp^+p^p+p fromPj_ 2 = 4.50 to 5.09 (GeV/c) 2 at 11.75 GeV/c. We used a 59%-polarized proton beam and a 71%-polarized proton target with both spins oriented perpendicular to the scattering plane. In these large-Pj 2 hard-scattering events, spin effects are very large and the ratio (dcr/dt) ^%(da/dt) ^ grows rapidly with increasing P± 2 , reaching a value of 4 at 90° (cm.). Thus, hard elastic scattering, which is presumably due to the direct scattering of the protons' constituents, may only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…The ratio of (dσ/dt) ↑↑ /(dσ/dt) ↑↓ with spin normal to the scattering plane can reach 4 at θ cm = 90 • [14]; the differential cross section dσ/dt oscillates around the scaling value [15]. The interference between the short-distance and long-distance (Landshoff) subprocesses due to soft gluon radiation [16] can explain the above spin-spin correlation and oscillatory scaling behavior [17,18].…”
mentioning
confidence: 95%
“…The ratio of (dσ/dt) ↑↑ /(dσ/dt) ↑↓ with spin normal to the scattering plane can reach 4 at θ cm = 90 • [14]; the differential cross section dσ/dt oscillates around the scaling value [15]. The interference between the short-distance and long-distance (Landshoff) subprocesses due to soft gluon radiation [16] can explain the above spin-spin correlation and oscillatory scaling behavior [17,18].…”
mentioning
confidence: 95%
“…Oscillations are not restricted to the pp elastic scattering channel; they are seen in elastic πp fixed angle scattering [14] and hints of oscillation about the s −7 scaling have also been reported in the recent data [5] from Jefferson Lab (JLab) on photo-pion production above the resonance region. In addition to violations of the scaling laws, spin correlations in polarized pp elastic scattering also show significant deviations from perturbative QCD (pQCD) expectations [15,16]. Several sets of arguments have been put forward to account for these deviations from scaling laws and the unexpected spin correlations.…”
mentioning
confidence: 99%
“…With the advent of QCD, the current wisdom based on perturbative contributions was that spin effects should generally be small as energy increases. However, a measurement by Krisch et al [107][108][109], indicated a large value of the spin-spin correlation A nn at 90…”
Section: Proton-proton Scattering and Other Similar Reactionsmentioning
confidence: 99%
“…This striking result of [107][108][109] motivated interesting studies on the underlying mechanisms. See, e.g., [65].…”
mentioning
confidence: 99%